Complex Skull Base Reconstructions in Kadish D Esthesioneuroblastoma: Case Report - Palejwala, Sheri K.; Sharma, Saurabh; Le, Christopher H.; Chang, Eugene; Erman, Audrey B.; Lemole, G. Michael, Jr (Journal of Neurological Surgery Reports, 2017)
Introduction Advanced Kadish stage esthesioneuroblastoma requires more extensive resections and aggressive adjuvant therapy to obtain adequate disease-free control, which can lead to higher complication rates. We describe the case of a patient with Kadish D esthesioneuroblastoma who underwent multiple surgeries for infectious, neurologic, and wound complications, highlighting potential preventative and salvage techniques.Case Presentation A 61-year-old man who presented with a large left-sided esthesioneuroblastoma, extending into the orbit, frontal lobe, and parapharyngeal nodes. He underwent margin-free endoscopic-assisted craniofacial resection with adjuvant craniofacial and cervical radiotherapy and concomitant chemotherapy. He then returned with breakdown of his skull base reconstruction and subsequent frontal infections and ultimately received 10 surgical procedures with surgeries for infection-related issues including craniectomy and abscess evacuation. He also had surgeries for skull base reconstruction and CSF leak, repaired with vascularized and free autologous grafts and flaps, synthetic tissues, and CSF diversion.Discussion Extensive, high Kadish stage tumors necessitate radical surgical resection, radiation, and chemotherapy, which can lead to complications. Ultimately, there are several options available to surgeons, and although precautions should be taken whenever possible, risk of wound breakdown, leak, or infection should not preclude radical surgical resection and aggressive adjuvant therapies in the treatment of esthesioneuroblastoma.
Keywords: esthesioneuroblastoma; olfactory neuroblastoma; skull base reconstruction; cerebrospinal fluid leak; pneumocephalus; sinonasal malignancy; complications